Business Cycles in Post-Conflict Serbia: The Cycle Is the Trend. Issue 4 (4th July 2018) - Suzuki, Tomoya
Abstract : As a hypothesis, "the cycle is the trend" means that business cycles are driven primarily by permanent productivity shocks that generate stochastic trends. This study estimates stochastic growth models for Serbia during the 2002Q2–2017Q2 and 2007Q1–2017Q2 periods, thereby accepting the hypothesis. Major findings are as follows. Migration outflows from Serbia to Germany negatively influenced permanent productivity shocks. Permanent productivity shocks were negatively correlated with remittances, which is also suggestive of the negative effect of migration outflows on permanent productivity shocks under the assumption that workers migrate to send money home. Labor market inefficiency pushes workers out of Serbia.